Integrated Learning Management in the Implementation of the Independent Curriculum at SDN Kagok 01 Tegal Regency - Suriswo, Suriswo; Abd Razak Bin Zakaria (EduBase : Journal of Basic Education, 2025)
The objective of this study was to analyze the planning, implementation, and assessment of integrated learning conducted by teachers at SDN Kagok 01, Tegal Regency, during the 2022/2023 academic year. Methods: This study used a qualitative approach. The subjects or respondents in this study were first-grade teachers and all first-grade students. Data collection techniques used included interviews, observation, and document analysis. The data analysis method applied in this study follows the model proposed by Miles and Huberman, which consists of data reduction, data presentation, and conclusion drawing (verification). The findings indicate that the learning planning process carried out by class teachers has been carried out effectively. In preparing for learning, teachers develop lesson plans using "Teaching Modules" (Modul Ajar or MA) as required by the Independent Curriculum. In addition, teachers prepare learning media or teaching aids for use in the classroom. Teaching materials are contextualized using real-world examples, in accordance with the principles of contextual learning. The implementation of the integrated learning program by class teachers has been effective. Integrated learning activities include introductory, core, and closing activities, all carried out systematically. In terms of assessment, teacher evaluation practices align with the lesson plan. These assessments include cognitive (knowledge-based) evaluations and skills-based or performance-based evaluations of student actions.